Phosphate fractionation from wastewater by a selectrodialysis process - Tran , Thi Kim Anh (Journal of Technical Education Science, 2018)
Phosphate recovery by crystallization has been a concern in recent years. However, to obtain a high efficiency in crystallization, the phosphate concentration in the influent stream is an important factor to control. This study aims at the fractionation and concentration of phosphate from synthetic water in selectrodialysis to increase the concentration as a pretreatment prior to crystallization. A lab-scale ion exchange membrane electrodialysis system (selectrodialysis) was used to perform the experiments. The results of selectrodialysis show that an increase in current density, initial pH of the product, and initial feed concentration of phosphate led to an increase in phosphate concentration in the product. The phosphate concentration in the product can reach 16 mM with a purity of phosphate 44%, the current efficiency to transport phosphate and chloride was 26.6% for a standard anion exchange membrane and 63% for a monovalent selective anion exchange membrane. Therefore, this study proves that the selectrodialysis is feasible and effective to fractionate phosphates from monovalent ions in the mixture.